Penerapan Association Rule-Market Basket Analysis (AR-MBA) Dalam Menentukan Strategi Product Bundling: Studi Kasus Pada Minimarket AKPRIND MART - Mustofa, Irfan; Wibowo, Agus Hindarto; Sekarjati, Kartinasari Ayuhikmatin; Makhulina, Nafis Sinta; Dewangga, Rio (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Data has become the most valuable component to be processed in order to provide usable information in the modern world of rapidly developing technology. When it comes to more in-depth or clear data analysis, technology is quite useful. Real governmental, social, and commercial operations use this technology; in the case of business, this is demonstrated by the quantity of minimarkets operating throughout Indonesia. As a result, it greatly increases commercial competition. Consequently, in order to compete, a study using the available data must be conducted. The Association Rule-Market Basket Analysis method was employed in this study to ascertain the shopping interests of the participants. According to the study's findings, two rules 60% (washing equipment and foodstuffs) and 62% (medicine and bottled drinks) showed the greatest confidence values. Based on these findings, the minimarket can decide what has to be done in terms of Product Bundling, setting up the layout and other tasks